Indonesian Celebrities Conversion: the Quest for Meaning and Social Environment - Gazi Saloom (Universitas Islam Negeri Mataram, 2019)
Religious conversion has often triggered a heated debate that pushes forward scholarly investigation. This paper is not based on a theological study of conversion, but a psycho-social exploration that aims to examine religious conversion among Indonesian celebrities and seeks factors that influence the conversion. This qualitative study selects five Indonesian celebrities who converted to Islam. All data and information were gathered from YouTube and the websites on entertainment and celebrity news. The study unveils that religious conversion is not a simple one-way process. Instead, it is a long process of search of meaning and identity, shaped by interpersonal relations and social interactions. Before conversion, the converts had made personal and colleague relationship with their Muslim friends and known Islam as it was manifested in everyday life through TV program, the call for Islamic prayer (adhān), neighborhood. The fact that Islam is the majority religion in the country has provided environments that further hastened the quest for the meaning of religion and identity amongst the celebrities.